Paper No P32: Impact of Halogen Ion Size of Chemical Agent System on Electrical and Optical Characteristics of rGO Layers. Issue 1 (September 2015) - Eskandari, V.; Fathollahi, M. R.; Mohajerani, E.; Fallahi, A.; Tahani, P.
Abstract In the current paper, we compare the effect of different hydrogen halide acid agent systems in chemical reduction of graphene oxide (GO) thin layers. We observe the large iodine ion can facilitate the reduction reaction in comparison with bromide and chloride counterpart ions. We show the sheet resistance of the graphene layer decreases by about six orders of magnitude due to efficient reduction of the graphene oxide.